2019
DOI: 10.14744/eej.2019.49369
|View full text |Cite
|
Sign up to set email alerts
|

A comparative ex-vivo study of effects of different irrigation protocols with/without laser activation on the root dentine’s micro-hardness

Abstract: To compare the effects of different irrigation protocols, with/without laser activation, on the radicular dentine's micro-hardness. Methods: Eighty-two human extracted premolars were decoronated and divided into 7 groups. Roots were longitudinally split into two halves. The micro-hardness was measured for one half before and after irrigation protocols. The groups were; G1: MTAD without laser-activation, G2: MTAD with laser-activation, G3: sodiumhypochlorite (SH) with laser-activation, G4: SH then EDTA with las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…In consistent with our results, Akbulut et al found that PIPS activation did not cause an additional decrease in dentin microhardness, indicating that the alterations in dentin mineral content and dentin microhardness were mainly affected by the irrigation solution, not by the activation technique [23]. Differently, Quteifani et al found that Er:Yag laser-activation (2 w power, 15 Hz frequency) of irrigants resulted in significantly less reduction of micro-hardness when compared to no-laser-activation [22]. This discrepancy may be related to the different laser parameters, which results in different degrees of changes in the chemical components [22].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In consistent with our results, Akbulut et al found that PIPS activation did not cause an additional decrease in dentin microhardness, indicating that the alterations in dentin mineral content and dentin microhardness were mainly affected by the irrigation solution, not by the activation technique [23]. Differently, Quteifani et al found that Er:Yag laser-activation (2 w power, 15 Hz frequency) of irrigants resulted in significantly less reduction of micro-hardness when compared to no-laser-activation [22]. This discrepancy may be related to the different laser parameters, which results in different degrees of changes in the chemical components [22].…”
Section: Discussionsupporting
confidence: 78%
“…The flow rate during CNI affects significantly the flow pattern within the root canal [ 32 ]. Unfortunately, this parameter was overlooked in most studies, and low flow rate was adopted [ 10 , 22 , 28 ]. Hardly any irrigant refreshment could be achieved apically to the needle when irrigating at a very low flow rate (0.02 mL/s), but a flow rate at 0.15–0.2 mL/s can provide refreshment up to 1 mm apically to the needle [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has wavelengths that range from 655 to 980 nm, which are suitable for dental use. The diode laser (810-980nm) has the capacity to penetrate dentinal tubules and reduce bacteria counts up to 500 μm depth (9) .…”
Section: Introductionmentioning
confidence: 99%
“…In actuality, these variables are related to a rise in the temperature of the dental tissues. As a result, the chemical and physical properties of dentin may change and microhardness may alter as a result of laser activation (9) . Accordingly, the study was intended to evaluate the effect of diode laser 980-nm on the microhardness of young and old root canal dentin after treatment with chemical solutions.…”
Section: Introductionmentioning
confidence: 99%